Extreme ultraviolet reflection film system based on high-refractive-index composite film and preparation method of extreme ultraviolet reflection film system
By introducing microporous structures into the Si-based high refractive index composite layer, the refractive index of the extreme ultraviolet reflective film system is improved and the extinction coefficient is reduced, and the problem of limited reflectivity of the extreme ultraviolet reflective film system in the prior art is solved, and a higher extreme ultraviolet reflectivity and lower extinction coefficient.
Patent Information
- Application Number
- CN202411564610.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The reflectivity of the existing extreme ultraviolet reflective films in the extreme ultraviolet light band is still limited, mainly due to the natural extreme ultraviolet optical characteristics of the material and the difficulty of fine control during the film plating process.
Using Si-based high-refractive index composite layer, by introducing microporous structures into the high-refractive index Si layer, the refractive index of the film layer is increased and the extinction coefficient is reduced, thereby increasing the refractive index difference between layers and reducing the optical image of the film layer with high-refractive index. Loss, achieving an improvement in the theoretical reflectivity of extreme ultraviolet.
The theoretical reflectivity of the extreme ultraviolet reflective film system is significantly improved, the extinction coefficient of the film layer is reduced, and the preparation process is simplified, which is suitable for large-area preparation.
Smart Images

Figure CN119471875A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of extreme ultraviolet optical reflective elements, and in particular relates to an extreme ultraviolet reflective film system based on a high-refractive index composite film and a preparation method thereof. Background Art
[0002] In recent years, the fields of extreme ultraviolet space astronomical observation, plasma diagnosis, extreme ultraviolet microscopic imaging and extreme ultraviolet lithography are booming, and extreme ultraviolet reflective optical components have become the most important optical components for applications in this band. Especially in the field of microelectronics, as ultra-large-scale integrated circuit manufacturing continues to develop in the direction of low thread, high integration and high performance, improving the resolution of extreme ultraviolet lithography technology has become a key technical problem in the domestic advanced chip manufacturing, thus putting forward higher requirements for the extreme ultraviolet reflective performance of the core component in the extreme ultraviolet light reflection system - the extreme ultraviolet reflective film system.
[0003] Specifically, extreme ultraviolet reflective optical elements need to produce the highest possible reflectivity for extreme ultraviolet light sources with wavelengths of 10-14nm, especially at 13.5nm. However, in this band, the refractive index of most materials is less than and close to 1, and the extinction coefficient is relatively large. Under near-normal incidence conditions, it is difficult to rely on a single layer of material to produce high extreme ultraviolet reflectivity. Therefore, researchers currently generally use a periodic multilayer film design in which high-refractive index materials and low-refractive index materials are alternately stacked, so that the extreme ultraviolet light produces a higher reflected light intensity at the film interface, and the Bragg reflection of a periodic film layer of a certain thickness is coherently superimposed, ultimately achieving extreme ultraviolet high reflectivity for the entire film system.
[0004] Therefore, in order to obtain a periodic stack with high reflectivity of extreme ultraviolet light, the refractive index difference between the selected film materials must be as large as possible, and the extinction coefficient of the two (i.e., light loss) should be as small as possible. At present, in the most representative Mo / Si extreme ultraviolet periodic multilayer film, the refractive index difference between Mo and Si in the extreme ultraviolet band can reach 0.06, and the extinction coefficient of the film layer is less than 0.01. In addition, the researchers have also explored other combinations of high and low refractive index materials, as well as reducing the interface roughness and interface interdiffusion of the film layer through optimization of the preparation process to improve the working efficiency of the extreme ultraviolet reflective film layer. However, the reflection intensity of the current extreme ultraviolet periodic film layer is still very limited by the extreme ultraviolet optical properties of natural materials and the fine control of the thin film coating process.
[0005] In order to improve the refractive index contrast of the film stacking unit, element doping is usually used in the multilayer film system to modify the material so as to obtain a high refractive index layer with a higher refractive index or a low refractive index layer with a lower refractive index. However, conventional material doping often makes it difficult to increase / reduce the refractive index of the film layer without affecting or even reducing the optical loss of the layer. For example, the doping of extreme ultraviolet high refractive index materials with relatively low extinction coefficients such as Ba and La into Si will inevitably increase its optical loss. This means that the refractive index and extinction coefficient of the target material must be weighed, and the precise control of the optical constants of the film is also a challenge, which has brought difficulties to the further improvement of the theoretical reflectivity of existing materials. In addition, the incorporation of external elements may cause additional film stress, surface roughness, and film interface matching. Therefore, developing a new film material design to improve the reflectivity of extreme ultraviolet light is the key to the development of extreme ultraviolet optical reflective elements and lithography technology. Summary of the invention
[0006] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide an extreme ultraviolet reflective film system based on a high-refractive index composite film and a preparation method thereof. The extreme ultraviolet reflective film system based on a high-refractive index composite film introduces a microporous structure into the high-refractive index Si layer to increase the refractive index of the film layer and reduce the extinction coefficient, thereby increasing the refractive index difference between layers and reducing the optical loss of the high-refractive index film layer, thereby achieving an improvement in the extreme ultraviolet theoretical reflectivity. At the same time, the deposition of the entire periodic film layer only adopts a magnetron sputtering process, which is convenient for actual preparation and system integration.
[0007] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:
[0008] An embodiment of the present invention provides an extreme ultraviolet reflective film system based on a high refractive index composite film, comprising a substrate, a periodic structure, a spacer layer and a protective film layer; a periodic structure including a film layer stacking unit repeatedly formed is arranged on the substrate, and a protective film layer is arranged on the periodic structure; the film layer stacking unit includes a low refractive index layer, a first Si spacer layer, a Si-based high refractive index composite layer and a second Si spacer layer arranged in sequence.
[0009] Preferably, the low refractive index layer comprises Mo, Mo2C, Nb or a MoNbC composite layer, more preferably Mo or MoC.
[0010] Preferably, in the Si-based high refractive index composite layer, the microporous structure is evenly distributed in the Si matrix in the form of independent nano units, and the volume proportion of the microporous structure is in the range of 10%-60%. The Si phase is used as the matrix phase, and the microporous structure is used as the membrane layer modified functional phase. Through the intermixing of different volume ratios, the refractive index of the Si-based high refractive index composite layer in the extreme ultraviolet band is maintained in the range of 0.99914-0.99964, which is greater than 0.99905 of pure Si, and the extinction coefficient of the Si-based high refractive index composite layer is 6.7×10 -4 -1.55×10 -3 range, lower than 1.72×10 -3 . The Si-based high-refractive-index composite layer uses a microporous-Si composite material to replace the traditional pure Si layer, which can effectively increase the refractive index of the high-refractive-index layer in the periodic film layer and reduce the extinction coefficient of this layer. As the volume percentage of the micropores increases, this trend becomes more obvious, that is, the refractive index of the composite layer is closer to 1 in vacuum, and the extinction coefficient tends to 0. At the same time, in order to ensure the stable existence of the microporous structure and the smooth plating of the periodic film structure, Si spacer layers are introduced above and below the Si-based high-refractive-index composite layer. These three-layer film structures and the low-refractive-index layer together constitute a periodic film stacking unit. The periodic film stacking unit is repeatedly prepared by magnetron sputtering deposition and ion-assisted technology to construct a high-reflectivity extreme ultraviolet periodic film layer.
[0011] Preferably, in the Si-based high refractive index composite layer, the volume proportion of the microporous structure is in the range of 20%-40%, ensuring that the optical constants of the composite film layer meet the requirements. If the volume proportion of the micropores is too small, the metal phase may be coated and cannot be etched, while if the proportion is too large, the Si phase structure may be unstable. Ideally, the larger the proportion of micropores, the higher the optical refractive index and the lower the extinction coefficient, but the actual situation is limited by the material structure. Within the preferred structural range (micropore proportion of 20%-40%), the refractive index and thickness of the film layer can be flexibly designed and matched to achieve extreme ultraviolet high reflectivity.
[0012] Preferably, the thickness of the low refractive index layer is 2.2-3.2 nm. The thickness of the first Si spacer layer is 0.2-0.7 nm, more preferably 0.3-0.6 nm. The thickness of the Si-based high refractive index composite layer is 2.2-4.2 nm. The thickness of the second Si spacer layer is 0.2-0.7 nm, more preferably 0.3-0.6 nm.
[0013] Preferably, the number of cycles set for the multiple repetitions of the film layer stacking unit is 40-60, and the multiple repetitions of the film layer stacking unit are used to obtain an optical path accumulation of an integer multiple of a quarter wavelength, satisfying a condition of constructive interference.
[0014] Preferably, the thickness of the protective film layer is 1-5 nm, and the function of the protective film layer is to prevent oxidation of the upper film layer and carbon deposition under extreme ultraviolet light irradiation.
[0015] Preferably, the protective film layer is Ru, and the protective film layer may also be carbides such as B4C, SiC, MoC, and borides such as Mo2B.
[0016] Preferably, the substrate is a single crystal silicon wafer, quartz glass or silicon carbide.
[0017] Preferably, the surface roughness of the entire film system is controlled within 0.05-0.35 nm to ensure the final reflective performance, and more preferably within 0.05-0.20 nm.
[0018] In summary, an embodiment of the present invention provides an extreme ultraviolet reflective film system based on a high refractive index composite film, wherein the Si-based high refractive index composite layer is used, by co-sputtering immiscible metals (Au, Ag, Al or Bi) and Si, regulating the co-growth behavior of the two phases, self-organizing and growing an orderly arranged metal nanostructure between Si phases, and then using external ion-assisted bombardment to selectively etch the metal phase to obtain a composite film of Si and microporous structure. By introducing vacuum into the Si phase, the equivalent refractive index of the layer can be effectively increased, making it close to vacuum, obtaining a higher refractive index contrast between films, ensuring a sufficiently large refractive index difference between layers, and reducing the extinction coefficient of the film layer, thereby pursuing a higher extreme ultraviolet reflectivity. More importantly, the introduction of a subwavelength-scale microporous structure has little effect on the extreme ultraviolet light reflection characteristics of the periodic film layer. In addition, replacing the traditional Si layer with a Si-based high refractive index composite layer has no effect on the optimization of the surface interface morphology and the control of roughness. The interface roughness of the film stacking unit and the microstructure in the film can also be flexibly controlled by adjusting the sputtering parameters.
[0019] To achieve the above-mentioned purpose of the invention, an embodiment of the present invention further provides a method for preparing an extreme ultraviolet reflective film system based on a high refractive index composite film, comprising the following steps:
[0020] (1) Pre-treating the substrate;
[0021] (2) selecting a target material, controlling the Mo, Mo2C, Nb or MoNbC target to work, and performing magnetron co-sputtering deposition on the substrate surface pretreated in step (1) to obtain a Mo, Mo2C, Nb or MoNbC low refractive index layer; then controlling the Si target to work, and sputtering depositing a first Si spacer layer on the low refractive index layer; then controlling the Au, Ag, Al or Bi metal target and the Si target to work simultaneously, and performing magnetron co-sputtering deposition on the first Si spacer layer to obtain a metal-Si phase-separated nanostructure, and then bombarding the film layer with an external ion source to selectively etch the metal phase, leaving a microporous structure, to obtain A Si-based high-refractive index composite layer is obtained; then the Si target is controlled to work, and a second Si spacer layer is sputtered and deposited on the surface of the Si-based high-refractive index composite layer; then the second Si spacer layer is smoothed by external ion-assisted bombardment; a film layer stacking unit including a low-refractive index layer, a first Si spacer layer, a Si-based high-refractive index composite layer and a second Si spacer layer is obtained; then, the aforementioned process is repeated, the film layer stacking unit is repeatedly plated for multiple times, and a Ru, B4C, SiC, MoC or Mo2B protective film layer is continuously sputtered on the last film layer stacking unit to complete the preparation of an extreme ultraviolet reflective film system based on a high-refractive index composite film.
[0022] Preferably, the pretreatment of the substrate includes ultrasonic cleaning with acetone, isopropanol and deionized water or immersion in piranha solution, followed by heating desorption and plasma etching cleaning to optimize the cleanliness of the substrate surface. After the above pretreatment, the substrate surface is more conducive to the growth of a smooth film layer.
[0023] Preferably, a DC, DC pulse or RF power source is used to drive the target. Further preferably, the magnetron sputtering of the metal target is preferably DC pulse or RF magnetron sputtering, and the magnetron sputtering of other targets is preferably DC magnetron sputtering, which is easy to control the performance of each film layer; the sputtering working gas is high-purity argon; the sputtering pressure range is 0.1-0.3 Pa, more preferably 0.13-0.17 Pa, so that the energy of the deposited particles is appropriate and the sputtering process is more stable; the background vacuum is 1.0×10 -4 Pa or less, preferably 7×10 -5 Pa and below is conducive to controlling the oxygen content in the film layer and ensuring the excellent optical properties of each film layer.
[0024] Preferably, when sputtering the low refractive index layer, the power density used by the target is in the range of 5-10 W / cm 2 , preferably 7-9W / cm 2 , which can make the roughness of the low refractive index layer and its optical constants beneficial to the periodic film layer to obtain a higher extreme ultraviolet light reflectivity.
[0025] Preferably, when sputtering the first Si spacer layer and the second Si spacer layer, the power density used by the Si target is in the range of 2-10 W / cm2 , preferably 4-8W / cm 2 , which can enable the obtained Si spacer layer to be continuously formed and ensure good roughness, which is beneficial to the interface sharpness and smooth plating of the periodic film layer.
[0026] Preferably, when sputtering and depositing the Si-based high refractive index composite layer, the power density used by the Si target is in the range of 2-10 W / cm 2 , more preferably 4-8W / cm 2 ; The power density range of the metal target is 0.5-3W / cm 2 , more preferably 1-2.5W / cm 2 By regulating the power density of the Si target and the metal target in the sputtering process, combined with the matching regulation of the sputtering gas pressure, the proportion and arrangement of the metal nanostructure in the metal-Si phase separation mixed layer can be easily adjusted over a large range, and its microstructure can be regulated. After obtaining the metal-Si phase separation mixed layer, the film is bombarded with external ion assistance, and the power density is set to 1-20W / cm by utilizing the binding energy difference between metal and Si atoms. 2 , preferably 3-15W / cm 2 , selectively etching the metal phase, retaining the Si phase, and smoothing the microporous surface, a well-structured microporous-Si hybrid film, i.e., a Si-based high-refractive index composite layer, is obtained. The Si-based high-refractive index composite layer with different microstructural characteristics is matched with the low-refractive index layer of different thicknesses to achieve the expected extreme ultraviolet reflectivity, thereby obtaining a high-reflectivity extreme ultraviolet periodic film layer.
[0027] Preferably, when sputtering the protective film layer, the power density used by the Ru, B4C, SiC, MoC or Mo2B target is in the range of 7-12 W / cm 2 , preferably 7-10W / cm 2 , which can make the obtained protective film layer have better film flatness and optical constants.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention adopts the method of directly combining extreme ultraviolet high refractive index material Si with high vacuum, starting from the self-assembly growth of metal-Si phase separation mixed film, assisted by external ion energy bombardment, to remove the metal phase, retain the Si phase, and smooth the microporous surface interface, thereby obtaining a well-structured microporous-Si mixed film, that is, a new Si-based high refractive index composite layer, ensuring that the interface refractive index difference within the film layer stacking unit in the periodic structure is large and the film layer roughness is effectively controlled.
[0030] (2) For the Si-based high-refractive-index composite layer, micropores are introduced into the Si phase, so that the refractive index and extinction coefficient in the extreme ultraviolet band are better than those of Si materials and very close to vacuum. Through the intermixing of different volume ratios, the refractive index in the extreme ultraviolet band is maintained in the range of 0.99914-0.99964, and the extinction coefficient is within 0.67×10 -3 -1.55×10 -3 range; the microporous-Si hybrid film, as a high refractive index layer material, can effectively meet the requirements of large refractive index difference and low extinction coefficient. It has a significant effect on improving reflectivity in the application of extreme ultraviolet multilayer films and provides material support for the construction of new extreme ultraviolet multilayer films.
[0031] (3) The spacer layer is made of the same material Si as the parent phase in the Si-based high-refractive index composite layer, thereby simplifying the preparation process and making it easy to control the refractive index matching and extreme ultraviolet reflection characteristics of the entire multilayer film.
[0032] (4) The present invention adopts magnetron co-sputtering and external ion-assisted sputtering to directly obtain a Si-based high-refractive index composite layer. Not only is the preparation process simple, low-cost, and suitable for large-area preparation, but more importantly, its nanostructure can be easily controlled by deposition parameters, and the optical constants of the composite layer can be flexibly designed, thereby increasing the design freedom of the film layer to obtain extreme ultraviolet high reflectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 is a schematic structural diagram of an extreme ultraviolet reflective film system based on a high refractive index composite film provided by an embodiment of the present invention;
[0035] Figure 2 is a schematic structural diagram of a Si-based high refractive index composite layer provided in an embodiment of the present invention;
[0036] Figure 3 It is a flow chart of a method for preparing an extreme ultraviolet reflective film system based on a high refractive index composite film provided by an embodiment of the present invention;
[0037] Figure 4 Schematic diagram of theoretical reflectivity curves of extreme ultraviolet reflective film systems prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2;
[0038] The specific symbols in the accompanying drawings are:
[0039] 100, substrate; 101, periodic structure; 102, protective film layer; 103, film layer stacking unit; 104, Mo low refractive index layer; 105, first Si spacer layer; 106, Si-based high refractive index composite layer; 107, second Si spacer layer. DETAILED DESCRIPTION
[0040] To make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.
[0041] The inventive concept of the present invention is: in view of the current situation that the refractive index difference between layers of thin films in the design of high-reflectivity extreme ultraviolet multilayer films is small and the interface reflectivity is low, the alloying strategy still has problems such as difficulty in precise preparation and trade-off of optical constants. The embodiment of the present invention provides an extreme ultraviolet reflective film system based on a high-refractive index composite film and a preparation method thereof, wherein a Si-based high-refractive index composite layer and a Mo low-refractive index layer are used as high-low refractive index contrast layers, and Si spacer layers are added above and below the Si-based high-refractive index composite layer to jointly form a film layer stacking unit and repeatedly form a periodic structure, thereby effectively improving the refractive index of the traditional Si high-refractive index layer and reducing its extinction coefficient, ensuring a high refractive index difference and a low extinction coefficient at the interface of the film layer stacking unit in the periodic structure, and selecting a Ru material that is resistant to ultraviolet radiation for the protective film layer, and finally obtaining an extreme ultraviolet periodic film layer with high reflectivity performance, with a simple preparation process and low cost, and suitable for large-area preparation in practical applications.
[0042] Figure 1 FIG. 1 is a schematic diagram of the structure of an extreme ultraviolet reflective film system based on a high refractive index composite film provided by an embodiment of the present invention. Figure 1 As shown, the embodiment provides an extreme ultraviolet reflective film system based on a high refractive index composite film, comprising a smooth substrate 100, a periodic structure 101 formed by repeated film layer stacking units 103, and a protective film layer 102 is arranged on the periodic structure 101; the film layer stacking unit 103 comprises a Mo low refractive index layer 104, a first Si spacer layer 105, a Si-based high refractive index composite layer 106 and a second Si spacer layer 107 arranged in sequence. Figure 2 As shown, in the Si-based high refractive index composite layer 106, the microporous structure is introduced into the matrix Si phase as a high refractive index functional phase. The Mo low refractive index layer 104 is prepared by direct magnetron sputtering deposition of Mo target, the first Si spacer layer 105 and the second Si spacer layer 107 are prepared by direct magnetron sputtering deposition of Si target, the Si-based high refractive index composite layer 106 is prepared by magnetron co-sputtering deposition of Si target and metal target plus ion bombardment technology, and the protective film layer 102 is prepared by direct magnetron sputtering deposition of Ru target.
[0043] Based on the same inventive concept, the embodiment also provides a method for preparing an extreme ultraviolet reflective film system based on a high refractive index composite film, such as Figure 3 As shown, the following steps are included:
[0044] S1, pre-treating the substrate 100.
[0045] In the embodiment, the substrate 100 is ultrasonically cleaned with acetone, isopropanol and deionized water (or immersed in piranha solution) in sequence, and then heated for desorption and plasma etching cleaning to optimize the surface cleanliness of the substrate 100. After the above pretreatment, the surface of the substrate 100 is more conducive to the growth of a smooth multilayer film.
[0046] S2, magnetron sputtering a Mo low refractive index layer 104.
[0047] Mo is selected as the target material, and the Mo target is controlled to work. Magnetron co-sputtering deposition is performed on the surface of the substrate 100 pretreated in step S1. The power density range of the Mo target is 5-10 W / cm 2 , preferably 7-9W / cm 2 , obtaining a Mo low refractive index layer 104.
[0048] S3 , magnetron sputtering the first Si spacer layer 105 .
[0049] Si is selected as the target material, and the Si target is controlled to work. The first Si spacer layer 105 is deposited on the Mo low refractive index layer 104 by magnetron sputtering. The power density range of the Si target is 2-10 W / cm 2 , preferably 4-8W / cm 2 , obtaining a first Si spacer layer 105.
[0050] S4, magnetron co-sputtering metal-Si phase-separated mixed layer.
[0051] Si and an immiscible metal (such as Au, Ag, Al or Bi) are selected as co-sputtering targets, and the Si target and the metal target are controlled to work. A self-organized metal-Si phase-separated mixed layer is deposited on the Si spacer layer 105 by magnetron sputtering. The power density used by the Si target is in the range of 2-10 W / cm 2 , preferably 4-8W / cm 2 The power density range of the metal target is 0.5-3W / cm 2 , preferably 1-2.5W / cm 2 .
[0052] S5, ion-assisted etching of the metal phase is performed to obtain a microporous-Si mixed Si-based high refractive index composite layer 106.
[0053] Apply ion-assisted bombardment to the metal-Si phase separation mixed layer, setting the power density to 1-20W / cm 2 , preferably 3-15W / cm 2 , to selectively etch away the metal phase while retaining the Si phase, thereby obtaining a Si-based high-refractive index composite layer 106 in which Si and micropores are mixed.
[0054] S6, magnetron sputtering a second Si spacer layer 107.
[0055] Si is selected as the target material, and the Si target is controlled to work. The second Si spacer layer 107 is deposited on the Si-based high refractive index composite layer 106 by magnetron sputtering. The power density range of the Si target is 2-10 W / cm 2 , preferably 4-8W / cm 2 , obtain the second Si spacer layer 107, continue to apply external ion-assisted bombardment on the second Si spacer layer 107, and set the power density to 0.5-10W / cm 2 , preferably 1-5W / cm 2 , to smooth the film layer, and obtain a film layer stacking unit 103 including a Mo low refractive index layer 104, a first Si spacer layer 105, a Si-based high refractive index composite layer 106 and a second Si spacer layer 107.
[0056] S7, repeatedly sputtering Mo low refractive index layer / first Si spacer layer / Si-based high refractive index composite layer / second Si spacer layer to obtain a periodic film layer.
[0057] Repeat the above process steps S2-S6 to plate 30-70 layers of film layer stacking units 103 including Mo low refractive index layer 104, first Si spacer layer 105, Si-based high refractive index composite layer 106 and second Si spacer layer 107 according to the number of periods to obtain a periodic structure 101.
[0058] S8 , magnetron sputtering the protective layer 102 .
[0059] Ru is selected as the target material, and a Ru protective film layer 102 is continuously sputtered on the top layer of the periodic structure 101. The power density range of the Ru target is 7-12 W / cm 2 , preferably 7-10W / cm 2 , and finally completed the preparation of extreme ultraviolet reflective film system based on high refractive index composite film.
[0060] The preparation method and characteristics of the extreme ultraviolet reflective film system based on the high refractive index composite film prepared by the present invention are described below in combination with the following Examples 1 and 2 and Comparative Examples 1 and 2. In the following examples, a silicon wafer or a quartz wafer is used as the substrate 100, the low refractive index layer material in the multilayer film is Mo material, the high refractive index layer is a Si-based composite material, and the material of the surface protection film layer 102 is Ru. By adjusting the relevant sputtering parameters, changing the micropore structure and distribution in the Si-based high refractive index composite layer 106, and combining the adjustment of the micropore volume percentage, an extreme ultraviolet reflective film system is prepared. Based on the transfer matrix method, MATLAB software is used to carry out theoretical calculations on the theoretical reflection spectra of the periodic film layers involved in the embodiments and comparative examples, and its reflection characteristics to extreme ultraviolet light are analyzed.
[0061] Example 1
[0062] In this embodiment, an ultra-smooth single-crystal silicon wafer is used as the substrate 100, and its surface roughness is 0.30 nm. The silicon wafer is placed in acetone, isopropanol and deionized water in turn, ultrasonically cleaned and dried with nitrogen, and the silicon wafer is fixed on a tray; the tray is placed in the deposition chamber of the magnetron sputtering equipment and pre-vacuumed to 7×10 -5 Below Pa, argon gas is introduced, and Mo target, Si target, and Ru target are cleaned by DC sputtering, and Au target is cleaned by DC pulse sputtering, and plasma bombardment is applied to clean the silicon wafer; after the etching and cleaning is completed, the argon gas flow is adjusted to make the pressure in the deposition chamber reach 0.16Pa.
[0063] Turn off the power supply of Si target, Ru target and Au target, and adjust the sputtering power density of Mo target to 7W / cm 2 , complete the magnetron sputtering of the Mo low refractive index layer 104. Turn off the Mo target power supply, start the Si target at the same time, and adjust the sputtering power density of the Si target to 5W / cm 2 , complete the magnetron sputtering of the first Si spacer layer 105. Start the Si target and Au target power supplies, and adjust the sputtering power density of the Si target and Au target to 5W / cm 2 and 1W / cm 2 , where the Si target and the Au target are tilted toward each other at a certain angle to complete the magnetron co-sputtering deposition of the Au-Si phase separation mixed layer. Turn off the Si target and Au target drive power, and start the external ion-assisted sputtering device at the same time, with the power density set to 12W / cm 2 , continuously bombarding the newly deposited Au-Si phase separation mixed layer to form a Si-based high refractive index composite layer 106 mixed with Si and micropores. Turn off the Au target power supply, start the Si target at the same time, and adjust the sputtering power density of the Si target to 5W / cm 2 , complete the magnetron sputtering of the second Si spacer layer 107 to obtain the film stack unit 103. Start the external ion-assisted sputtering device and set the power density to 2W / cm2 , bombarding the newly deposited second Si spacer layer 107. Then, the deposition of the Mo / Si / Si-based composite layer / Si film layer stacking unit 103 is repeated 41 times to complete the plating of the entire periodic structure 101 (a total of 41 layers of Mo / Si / Si-based composite layer / Si film layer stacking units 103), and then the Ru target driving power supply is started again, and the power density is set to 8W / cm 2 , a Ru protective film layer 102 is deposited, and finally an extreme ultraviolet periodic film layer with high reflectivity characteristics is obtained.
[0064] Through the characterization and analysis of the corresponding components and microstructures, the surface roughness of the above-mentioned extreme ultraviolet reflective film system is 0.17nm, the thickness of the Mo low refractive index layer 104 in the film system is 2.7nm, the thickness of the first Si spacer layer 105 and the second Si spacer layer 107 are both 0.5nm, and the thickness of the Si-based high refractive index composite layer 106 is 3.2nm, that is, the thickness of the Mo / Si / Si-based composite layer / Si film layer stacking unit 103 is 6.9nm, and the thickness of the Ru protective film layer 102 is 1.2nm. The volume percentage of micropores in the Si-based high refractive index composite layer 106 is 41%, of which the micropore structure size is 3.0nm, the micropore unit gap is 1.2nm, and it is diffusely distributed in the Si matrix. At the same time, based on the analysis of the effective medium theory, the equivalent refractive index of the Si-based high refractive index composite layer 106 in the extreme ultraviolet band is at the level of 0.99963, and the extinction coefficient is 1.03×10 -3 The theoretical reflectivity of the 13.5nm extreme ultraviolet light can reach more than 76.7%. Figure 4 shown.
[0065] Example 2
[0066] In this embodiment, an ultra-smooth single-crystal silicon wafer is used as the substrate 100, and its surface roughness is 0.30 nm. The silicon wafer is placed in acetone, isopropanol and deionized water in turn, ultrasonically cleaned and dried with nitrogen, and the silicon wafer is fixed on a tray; the tray is placed in the deposition chamber of the magnetron sputtering equipment and pre-vacuumed to 7×10 -5 Below Pa, argon gas is introduced, and Mo target, Si target, and Ru target are cleaned by DC sputtering, and Ag target is cleaned by DC pulse sputtering, and plasma bombardment is applied to clean the silicon wafer; after the etching and cleaning is completed, the argon gas flow is adjusted to make the pressure in the deposition chamber reach 0.16Pa.
[0067] Turn off the power supplies of Si target, Ru target and Ag target, and adjust the sputtering power density of Mo target to 7.5W / cm 2 , completing the magnetron sputtering of the Mo low refractive index layer 104. Turn off the Mo target power supply, start the Si target at the same time, and adjust the sputtering power density of the Si target to 6.2 W / cm 2, completing the magnetron sputtering of the first Si spacer layer 105. Start the Si target and Ag target power supplies, and adjust the sputtering power density of the Si target and the Ag target to 6.2 W / cm 2 and 1W / cm 2 , where the Si target and the Ag target are tilted toward each other at a certain angle to complete the magnetron co-sputtering deposition of the Ag-Si phase separation mixed layer. Turn off the Si target and Ag target drive power, and start the external ion-assisted sputtering device at the same time, with the power density set to 11W / cm 2 The Ag-Si phase separation mixed layer just deposited is continuously bombarded to form a microporous-Si mixed Si-based high refractive index composite layer 106. The Ag target power supply is turned off, and the Si target is started at the same time. The sputtering power density of the Si target is adjusted to 6.2 W / cm 2 , complete the magnetron sputtering of the second Si spacer layer 107. Start the external ion-assisted sputtering device and set the power density to 2W / cm 2 , bombarding the newly deposited second Si spacer layer 107. Obtaining the film stack unit 103. Then continue to repeat the above Mo / Si / Si-based composite layer / Si film stack unit 103 deposition 50 times to complete the plating of the entire periodic structure 101 (a total of 50 layers of Mo / Si / Si-based composite layer / Si film stack unit 103), and then start the Ru target drive power supply again, and the power density is set to 8.2W / cm 2 , a Ru protective film layer 102 is deposited, and finally an extreme ultraviolet periodic film layer with high reflectivity characteristics is obtained.
[0068] Through the characterization and analysis of the corresponding components and microstructures, the surface roughness of the above-mentioned extreme ultraviolet reflective film system is 0.14nm, the thickness of the Mo low refractive index layer 104 in the film system is 2.5nm, the thickness of the first Si spacer layer 105 and the second Si spacer layer 107 are both 0.4nm, and the thickness of the Si-based high refractive index composite layer 106 is 3.6nm, that is, the thickness of the Mo / Si / Si-based composite layer / Si film layer stacking unit 103 is 6.9nm, the thickness of the Ru protective film layer 102 is 1.6nm, and the volume percentage of micropores in the Si-based high refractive index composite layer 106 is 22%, of which the micropore structure size is 2.2nm, and the micropore unit gap is 2.0nm. Based on the analysis of the effective medium theory, the equivalent refractive index of the Si-based high refractive index composite layer 106 in the extreme ultraviolet band is 0.99924, and the extinction coefficient is 1.38×10 -3 The theoretical reflectivity of 13.5nm extreme ultraviolet light can reach more than 71.2%. Figure 4 shown.
[0069] Comparative Example 1
[0070] The EUV reflective film system is plated according to the preparation process and film structure of Example 1, except that the film layer stacking unit 103 uses Mo / Si / Si / Si to replace the Mo / Si / Si-based composite layer / Si in Example 1, and no microporous structure is introduced.
[0071] Comparative Example 2
[0072] The EUV multilayer film is deposited according to the preparation process and film structure of Example 2, except that the film layer stacking unit 103 uses MoC / Si / Si / Si to replace the Mo / Si / Si-based composite layer / Si in Example 2, and no microporous structure is introduced.
[0073] Comprehensive analysis of the above embodiments and comparative examples, Figure 4 At the same time, the theoretical reflectivity curves of the extreme ultraviolet reflective film systems prepared in Example 1, Example 2 and Comparative Example 1, Comparative Example 2 are given. Based on the theoretical reflectivity curves, the theoretical reflectivities of the extreme ultraviolet multilayer films prepared in Example 1, Example 2 and Comparative Example 1, Comparative Example 2 to 13.5nm extreme ultraviolet light are extracted and listed in Table 1 for comparison.
[0074] Table 1 Theoretical reflectivity of the EUV multilayer films prepared in Examples 1, 2 and Comparative Examples 1, 2 to 13.5 nm EUV light:
[0075] project Example 1 Comparative Example 1 Example 2 Comparative Example 2 Theoretical reflectivity 76.75% 73.64% 71.25% 69.71%
[0076] In summary Figure 4 The comparison results of the theoretical reflectivity curve and the theoretical reflectivity in Table 1 show that the extreme ultraviolet film system prepared by the embodiment of the present invention has a higher theoretical reflectivity than the existing extreme ultraviolet multilayer film. Specifically, the comparison of the results between Example 1 and Comparative Example 1 and between Example 2 and Comparative Example 2 shows that the high refractive index layer uses a Si-based composite layer to replace the traditional pure Si layer, which can effectively improve the equivalent refractive index of the film layer and reduce the extinction coefficient of the film layer. At the same time, compared with the Si layer, the microstructure characteristics and optical constants of the Si-based high refractive index composite layer can be directly regulated by sputtering parameters, and the trade-off between the refractive index and extinction coefficient of the thin film brought about by conventional alloying and the interface matching problem between the film layers are well solved. The combined effect of the above effects ultimately improves the reflection ability of the extreme ultraviolet reflective film system based on the high refractive index composite film proposed in the embodiment of the present invention. The preparation method provided by the embodiment of the present invention has a simple preparation process, low cost, and is suitable for large-area preparation in practical applications. The nanocolumn structure is easily directly regulated by the deposition parameters, and the optical constants of the composite layer can be flexibly designed, thereby improving the design freedom of the film system to obtain extreme ultraviolet high reflectivity.
[0077] The specific implementation methods described above have described in detail the technical solutions and beneficial effects of the present invention. It should be understood that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An extreme ultraviolet reflective film system based on a high refractive index composite film, characterized in that: It includes a substrate, a periodic structure and a protective film layer; a periodic structure including a film layer stacking unit repeatedly formed is arranged on the substrate, and a protective film layer is arranged on the periodic structure; the film layer stacking unit includes a low refractive index layer, a first Si spacer layer, a Si-based high refractive index composite layer and a second Si spacer layer arranged in sequence, and a microporous structure is introduced into the matrix Si phase of the Si-based high refractive index composite layer as a high refractive index functional phase.
2. The extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 1, characterized in that: The low refractive index layer includes Mo, Mo2C, Nb or a MoNbC composite layer.
3. The extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 1, characterized in that: In the Si-based high refractive index composite layer, the volume proportion of the microporous structure ranges from 10% to 60%.
4. The extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 1, characterized in that: The thickness of the low refractive index layer is 2.2-3.2 nm, the thickness of the first Si spacer layer is 0.2-0.7 nm, the thickness of the Si-based high refractive index composite layer is 2.2-4.2 nm, and the thickness of the second Si spacer layer is 0.2-0.7 nm.
5. The extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 1, characterized in that: The film layer stacking unit is repeated multiple times and the number of cycles is 30-70.
6. The extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 1, characterized in that: The protective film layer includes Ru, B4C, SiC, MoC or Mo2B, and has a thickness of 1-5nm.
7. The extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 1, characterized in that: The surface roughness of the film system is 0.05-0.35nm.
8. A method for preparing an extreme ultraviolet reflective film system based on a high refractive index composite film according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Pre-treating the substrate; (2) performing magnetron co-sputtering deposition on the surface of the substrate pretreated in step (1) to obtain a low refractive index layer; then controlling the Si target to work and sputtering depositing a first Si spacer layer on the low refractive index layer; then controlling the metal target and the Si target to work simultaneously and performing magnetron co-sputtering deposition on the first Si spacer layer to obtain a metal-Si phase separation mixed layer, and then using external ion-assisted bombardment of the film layer to selectively etch away the metal phase, leaving a mixed film of Si and microporous structure, to obtain a Si-based high refractive index composite layer; then controlling the Si target to work and sputtering depositing a second Si spacer layer on the surface of the Si-based high refractive index composite layer; then using external ion-assisted bombardment to smooth the second Si spacer layer; obtaining a film layer stacking unit including a low refractive index layer, a first Si spacer layer, a Si-based high refractive index composite layer, and a second Si spacer layer; Subsequently, the aforementioned process is repeated, the film layer stacking unit is repeatedly plated multiple times, and a protective film layer is further sputtered on the last film layer stacking unit to complete the preparation of the extreme ultraviolet reflective film system based on the high refractive index composite film.
9. The method for preparing an extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 8, characterized in that: The target is driven by DC, DC pulse or RF power. The sputtering gas is high-purity argon. The sputtering pressure range is 0.1-0.3Pa and the background vacuum is 1.0×10 -4 Pa and below.
10. The method for preparing an extreme ultraviolet reflective film system based on a high refractive index composite film according to claim 8, characterized in that: When sputtering Si-based high refractive index composite layers, the power density used by the Si target ranges from 2 to 10 W / cm 2 The power density range of the metal target is 0.5-3W / cm 2 .